Face recognition based on PCA algorithm - Lin, Lumeng (2017)
The purposed of this final year research project is to develop a computer system to recognize a person face by comparing the main characteristics of face to those of known faces in the database. The project is mainly focus on two dimensional images that are under controlled environment, such as brightness and background are consistent. The Principal Component Analysis (PCA) technique has been used in the face recognition system. And the programing language is C# for building graphic user interface (GUI) to perform intuitive design and simple use in recognition process. The report will cover the concept of PCA and Eigen face that be applied in the system, and illustrate the how the system is implemented, and also the various test to determine the recognition accuracy for further enhancement.